SISTEM HUKUM PENEGAKAN QANUN JINAYAH DI ACEH - Mahdi Mahdi (Sharia and Law Faculty, 2017)
There are, at least,three provincial regulations (qanun) have been enacted and stipulated by Aceh Government dealing with jinayah (Islamic penal rules) during Islamic sharia law implementation in Aceh, i.e. qanun khamar (drunk), qanun maisir (gambling), and qanun khalwat (immoral). From 2004 to 2008, much of the conflict subjects with the qanun jinayah have been determined by judge of Islamic Court (Mahkamah Syarâ€™iyah) Aceh, such as whip or fine. Since 2009 until now, some cases regarding qanun khalwat have been sentenced through adat (tradition) court of Aceh. The important questions arise here: what are the obstacle factors of qanun jinayah enforcement in Aceh? What are implications of those obstacle factors within qanun jinayah enforcement in Aceh? And the last question, what kind of legal system within qanun jinayah enforcement in Aceh? By using qualitative research method, data resources gained from interview, library and observation, this research result indicates at least 6 (six) factors that could be obstacle factors of qanun jinayah enforcement in Aceh, namely, the substance of qanun jinayah is very weak; â€œpolitical willâ€ of Aceh Government to implement the regulations seems not seriously; there are many different perceptions about qanun jinayah around Aceh citizens and students; integrity and morality of law enforcer are very weak; public pressure is very restricted; and budgeting for Islamic sharia law implementation is very small. The implication from this causes trend toward unclear of law, escalating radicalism to subject conflict of qanun jinayah, and debate about qanun jinayah enforcement. For khalwat cases, the legal system enforcement in Aceh due to adat judicial system. Meanwhile, for maisir (gambling) and khamar (drunk) cases based on Mahkamah Syarâ€™iyah system.